Implementasi Strategi Pemerintah Kota Bogor Dalam Meningkatkan Pertumbuhan Ekonomi Daerah Melalui Pembangunan Kota Ramah Keluarga - Lestari, Nurmala Suci; Suyaman, Dede Jajang (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study aims to describe the implementation of strategies in realizing a family-friendly city in the Bogor City Government using research methods through a descriptive qualitative approach. The results showed that there were four programs that were intensified by the Bogor City Government to improve the regional economy and create a family-friendly city, namely Bogor Lancar, Bogor Merenah, Bogor Kasohor, and Bogor Samawa. From these four programs, the Bogor City Government not only succeeded in creating a family-friendly city, but also led Bogor City to become a city with an economic growth rate above the national average. The result of the implementation of these four programs in a span of approximately four years is the increase in economic growth in Bogor City compared to the previous period, where the increase in economic growth occurred at 5.65%, which is certainly above the average value of national economic growth which only touched 5.31% and West Java economic growth which was only 5.45%. This achievement is obtained from increasing innovation and facilitating existing MSMEs so that they can contribute significantly to increasing regional economic growth.